(untitled) (The Pakistan Development Review, 2017)
“Looking Back: How Pakistan Became an Asian Tiger by 2050” is Nadeem Ul Haque’s latest book. The Kindle edition of the book is available from Amazon. The book, while dismissing the notion of ‘development first’, argues for ‘reforming the system first’ to make the ground conducive for sustainable development. The book, written as semifiction, imagines Pakistan as a developed country by year 2050. The United Nations, which sets up a commission in the year 2051 to understand Pakistan’s development model, narrates the development story